Metformin for the treatment of hidradenitis suppurativa: a little help along the way. (11th August 2012) - Verdolini, R.; Clayton, N.; Smith, A.; Alwash, N.; Mannello, B.
Abstract: Background  Despite recent insights into its aetiology, hidradenitis suppurativa (HS) remains an intractable and debilitating condition for its sufferers, affecting an estimated 2% of the population. It is characterized by chronic, relapsing abscesses, with accompanying fistula formation within the apocrine glandbearing skin, such as the axillae, ano‐genital areas and breasts. Standard treatments remain ineffectual and the disease often runs a chronic relapsing course associated with significant psychosocial trauma for its sufferers. Objective  To evaluate the clinical efficacy of Metformin in treating cases of HS which have not responded to standard therapies. Methods  Twenty‐five patients were treated with Metformin over a period of 24 weeks. Clinical severity of the disease was assessed at time 0, then after 12 weeks and finally after 24 weeks. Results were evaluated using Sartorius and DLQI scores. Results  Eighteen patients clinically improved with a significant average reduction in their Sartorius score of 12.7 and number of monthly work days lost reduced from 1.5 to 0.4. Dermatology life quality index (DLQI) also showed a significant improvement in 16 cases, with a drop in DLQI score of 7.6. Conclusion  Metformin helps control HS with minimal side effects and good patient compliance and can represent a further agent in the spectrum of treatments available in the treatment of this disease.